2022
DOI: 10.2196/27487
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Assessment of Oura Ring Nocturnal Heart Rate and Heart Rate Variability in Comparison With Electrocardiography in Time and Frequency Domains: Comprehensive Analysis

Abstract: Background Photoplethysmography is a noninvasive and low-cost method to remotely and continuously track vital signs. The Oura Ring is a compact photoplethysmography-based smart ring, which has recently drawn attention to remote health monitoring and wellness applications. The ring is used to acquire nocturnal heart rate (HR) and HR variability (HRV) parameters ubiquitously. However, these parameters are highly susceptible to motion artifacts and environmental noise. Therefore, a validity assessment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 44 publications
(58 reference statements)
0
51
0
Order By: Relevance
“…These different modes of activation may contribute to the observed differences in fluctuations of these bio signals under stress. HR and HRV parameters can be measured easily using a chest band, a smartwatch, or a ring [28] in everyday life or in laboratory settings making it a feasible approach for most research studies. However, our results suggest that among pregnant women, HRV parameters alone may not be adequate as an acute stress assessment tool but may benefit from other bio signals to help distinguish between stress and non-stress states more accurately.…”
Section: Principle Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These different modes of activation may contribute to the observed differences in fluctuations of these bio signals under stress. HR and HRV parameters can be measured easily using a chest band, a smartwatch, or a ring [28] in everyday life or in laboratory settings making it a feasible approach for most research studies. However, our results suggest that among pregnant women, HRV parameters alone may not be adequate as an acute stress assessment tool but may benefit from other bio signals to help distinguish between stress and non-stress states more accurately.…”
Section: Principle Resultsmentioning
confidence: 99%
“…Further details about the heart rate and HRV features calculation have been previously described [4]. The abnormal IBI and HRV values generated by motion artifacts were removed before proceeding with the analysis according to the removal criteria described in another study utilizing HRV measures [28]. The removal criteria are based on the normal range of HR and IBI values.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…The consumer-available ring contains 2 infrared Light-Emitting Diode (LED) sensors, 2 Negative Temperature Coefficient (NTC) thermistor sensors, a tri-axial accelerometer, and a gyroscope. Although the algorithms that are used by the Oura ring to classify sleep and HRV based on the outputs of these sensors are proprietary, the ring (generation 2) has been confirmed to provide valid measurements of TST [ 48 , 49 ] and HRV [ 25 , 50 , 51 ] in independent research. Participants used a ring-size kit to determine their correct ring size to optimize fit for both user comfort and measurement accuracy and were allowed to choose a ring color of their preference.…”
Section: Methodsmentioning
confidence: 99%
“…Validation studies indicated generally good accuracy of sleep-wake detection for the Oura ring, with small absolute error for total sleep time estimation compared to polysomnography (PSG; 87.8% of nights within 30-min error) [63], ambulatory electroencephalography (7.39% mean absolute percentage error) [64], and 94% accuracy for 2-stage detection (sleep, wake) compared to polysomnography for a simple accelerometerbased model and 96% for a full model using machine learning algorithm [62]. It could accurately measure nocturnal heart rate (HR) and average heart rate variability (RMSSD) in both the 5-min and average-per-night tests compared to an electrocardiogram device [65]. It also outperforms other wearable devices such as smartwatches [66].…”
Section: Sleep and Its Constituentsmentioning
confidence: 99%